Current Distribution and Input Impedance of a VLF Tubular Antenna in a Cold Plasma - Lina He; Tong He; Hui Ran Zeng; Kai Li (IEEE Access, 2020)
As the U.S. and Europe launched the very low frequency (VLF: 3-30 kHz) space-borne transmitting and propagation experiments during the past thirty years, space-borne antennas have been playing a more and more important role in contemporary VLF communication systems, which are very likely to become an indispensable approach for overwater/underwater communication and navigation in the future. In this paper, we propose a semianalytical method for evaluating the current distribution and input impedance of a VLF space-borne tubular antenna. By considering the effects of both the ordinary wave (O-wave) and the extraordinary wave (E-wave) in an anisotropic ionosphere, the analytical expression for the current distribution has a more complicated form and is derived via the method of moments (MoM) and the Gauss-Legendre quadrature (GLQ) algorithm. Computations show that the current distribution and input impedance under anisotropic conditions are very sensitive to parameter changes, but the overall trend for the input impedance will increase with the radius or electrical length of the antenna. Comparisons with linear models and numerical results obtained in FEKO verify the accuracy of this method. From simulations about the effect of the geomagnetic inclination angle to the input impedance, we advise that the parallel case can be preferred as an alternative for the best angle. Once all antenna parameters are determined, there is a possibility to find multiple optimal inclination angles. In addition, qualitative analyses of the impact of environmental changes to the antenna characteristics are also discussed.